Triple-Negative Breast Cancer A Clinician's Guide (Springer International Publishing, 2018)
This guide provides practical information that will assist clinicians involved in the diagnosis, assessment, treatment, and follow-up care of patients with triple-negative breast cancer. After opening chapters on pathologic evaluation, clinical presentation, genetics, and imaging features, the full range of current treatment approaches is thoroughly reviewed from a multidisciplinary perspective. Readers will find up-to-date information and guidance on surgical management, radiation therapy, tailored adjuvant therapy, neoadjuvant treatment, systemic treatment for metastatic disease, and molecular profiling and targeted therapy. The coverage is completed by discussion of special issues in young women and individualization of the management approach in older patients. All healthcare professionals who care for patients with triple-negative breast cancer will find the book to be an invaluable source of expert advice on the issues faced in real-world practice. .